2010
DOI: 10.1007/s10311-010-0300-4
|View full text |Cite
|
Sign up to set email alerts
|

Geochemical and ecological significance of soil lipids under Rhododendron ponticum stands

Abstract: The bio-geographical significance of Rhododendron ponticum spp. baeticum (Ericaceae) as a relict species is well recognized. However, out of its native habitat it is an invasive exotic considered a major threat to natural ecosystems in areas of Atlantic Western Europe. The studies on the impact of Rhododendron influence on soil organic matter composition and associated ecological implications, i.e. presence of bioactive compounds with ecological significance, are limited. This work describes the soil lipid ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Though R. ponticum can grow over a wide range of soils, it mostly thrives on podzolic sandy soils (Rotherham, 1983) while it poorly performs on brown soils (Esquivia, 1993). However, R. ponticum is well known for its recalcitrant, acidifying litter (Horuz et al, 2014; Jones et al, 2019), which also contains allelopathic compounds (Simons, 1988; González‐Pérez et al, 2011) that strongly reduce soil microbial activity (Sariyildiz & Küçük, 2009) and soil invertebrates (Malo et al, 2012). Due to deep‐shade conditions below R. ponticum canopies and the release of allelopathic compounds by the decaying litter, litter decomposition may be considerably slowed down.…”
Section: Discussionmentioning
confidence: 99%
“…Though R. ponticum can grow over a wide range of soils, it mostly thrives on podzolic sandy soils (Rotherham, 1983) while it poorly performs on brown soils (Esquivia, 1993). However, R. ponticum is well known for its recalcitrant, acidifying litter (Horuz et al, 2014; Jones et al, 2019), which also contains allelopathic compounds (Simons, 1988; González‐Pérez et al, 2011) that strongly reduce soil microbial activity (Sariyildiz & Küçük, 2009) and soil invertebrates (Malo et al, 2012). Due to deep‐shade conditions below R. ponticum canopies and the release of allelopathic compounds by the decaying litter, litter decomposition may be considerably slowed down.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies showed a link between biomarkers imprints in soil and plant diversity in the surrounding (Marseille et al, 1999;Trendel et al, 2010;González-Pérez et al, 2011;Zocatelli et al, 2012;Lavrieux et al, 2012;Ronkainen et al, 2013). In addition, the analysis of soil lipids revealed that biomarker imprints of soils can distinguish between pasture/grassland and forest (Zocatelli et al, 2012) and that the soil chemical legacy of former land uses can be preserved for decades (Lavrieux et al, 2012).…”
Section: Introductionmentioning
confidence: 99%